A combined low-frequency electromagnetic and fluidic stimulation for a controlled drug release from superparamagnetic calcium phosphate nanoparticles: potential application for cardiovascular diseases. Issue 144 (11th July 2018) - Marrella, Alessandra; Iafisco, Michele; Adamiano, Alessio; Rossi, Stefano; Aiello, Maurizio; Barandalla-Sobrados, Maria; Carullo, Pierluigi; Miragoli, Michele; Tampieri, Anna; Scaglione, Silvia; Catalucci, Daniele
Abstract : Alternative drug delivery approaches to treat cardiovascular diseases are currently under intense investigation. In this domain, the possibility to target the heart and tailor the amount of drug dose by using a combination of magnetic nanoparticles (NPs) and electromagnetic devices is a fascinating approach. Here, an electromagnetic device based on Helmholtz coils was generated for the application of low-frequency magnetic stimulations to manage drug release from biocompatible superparamagnetic Fe-hydroxyapatite NPs (FeHAs). Integrated with a fluidic circuit mimicking the flow of the cardiovascular environment, the device was efficient to trigger the release of a model drug (ibuprofen) from FeHAs as a function of the applied frequencies. Furthermore, the biological effects on the cardiac system of the identified electromagnetic exposure were assessed in vitro and in vivo by acute stimulation of isolated adult cardiomyocytes and in an animal model. The cardio-compatibility of FeHAs was also assessed in vitro and in an animal model. No alterations of cardiac electrophysiological properties were observed in both cases, providing the evidence that the combination of low-frequency magnetic stimulations and FeHAs might represent a promising strategy for controlled drug delivery to the failing heart.